[1, 2]-Rearrangement of iminium salts provides access to heterocycles with adamantane scaffold. Issue 26 (25th June 2020) - Zonker, Benjamin; Duman, Ediz; Hausmann, Heike; Becker, Jonathan; Hrdina, Radim
Abstract : A Wagner–Meerwein rearrangement of iminium triflate salts followed by a Friedel–Crafts reaction enables the synthesis of aza-heterocycles and amines with adamantane scaffold. Abstract : We describe a Brønsted acid-catalysed cascade reaction consisting of a Wagner–Meerwein rearrangement and a subsequent intra- or intermolecular Friedel–Crafts reaction leading to adamantane-based heterocycles. In contrast to the reported W.–M. rearrangements, in this case an iminium moiety serves as the acceptor of a migrating nucleophilic alkyl group in a [1, 2]-alkyl shift.